Cranio-Orbital and Orbitocranial Approaches to Orbital and Intracranial Disease: Eye-Opening Approaches for Neurosurgeons - Abou-Al-Shaar, Hussam; Krisht, Khaled M.; Cohen, Michael A.; Abunimer, Abdullah M.; Neil, Jayson A.; Karsy, Michael; Alzhrani, Gmaan; Couldwell, William T. (Frontiers in Surgery, 2020)
Orbital approaches for targeting intracranial, orbital, and infratemporal disease have evolved over the years in an effort to discover safe, reliable, effective, and cosmetically satisfying surgical corridors. The surgical goals of these approaches balance important factors such as proximity of the lesion to the optic nerve, the degree of anticipated manipulation and required space for surgical maneuverability, and the type of disease. The authors provide a comprehensive review of the most commonly used periorbital approaches in the management of intra- and extracranial disease, with emphasis on the advantages and limitations of each approach. Illustrative cases are provided to demonstrate the surgical procedures and technical nuances for diseases commonly treated by neurosurgeons.